Reflections on education and philosophy in Peru - Casquier-Ortiz, Jesús R. (2020)
This article provides a view about the education in Peru, where the ongoing teaching models are pointing to, and if there is a horizon thought and defined trough the philosophy. Since although there is talk of "missions" and "visions", in most cases it cannot be determined if these are the product of a reflection on pedagogy and didactics or if they are lethargic speculations as a result of bureaucratic marasmus and the conceptual hallucination around other educational models that are alien to Peru’s socio-cultural reality. Hence, to consider this concern, we begin this article by identifying the main characteristics around the different stages that education has gone through throughout the history of Peru, and thereafter it seeks to inquire about the current state of education. in Peru and the place of philosophy in it. Likewise, a reflective criticism is made about teaching in our country.